Ultrasonographic imaging on the progress of wound healing after abdominal surgery in dogs - Abu Bakar @ Zakaria, Md Zuki; Boyd, J. S. (Veterinary Association Malaysia, 2003)
The present study has been carried out with the aim of evaluating the progress of abdominal wound healing after abdominal surgery and to detect any changes that might occur during the reparative phase using B-mode ultrasound. Five dogs of different breeds, sex and age were used in this study. The dogs had undergone ventral abdominal surgery for various reasons. A real-time B-mode ultrasound machine (Capasee TOSHIBA) connected with a 7.5 MHz linear array transducer was used in this study. The ultrasonographic examination was done transversely across the ventral abdominal midline (wound) from cranial to caudal and longitudinal scan was done along the wound (incision site) from cranial to caudal. Initial scanning was carried out on day one (approximately 24 hours) post-operation. Subsequent scans were carried out on the basis of one day apart while the animal was still in the hospital. The ultrasonographic appearance of wound (surgical site) at the early stage was ill-defined hypoechoic with acoustic shadowing artefact. With time the wound appeared hypoechoic with some degree of an echogenic centre and casting acoustic shadowing artefact. By day 11 post-operation, the wound was found to have a disorganized echogenic structure with acoustic shadowing artefact. By day 13 post-operation, the wound appeared as disorganized hyperechoic with acoustic shadowing artefact due to the presence of fibrous tissue formation. Results from this study also demonstrate that the wound could be evaluated in both transverse and longitudinal scans. However, the transverse scan seems to be easier than the longitudinal scan in evaluation of the surgical wound.